Pulmonary Rehabilitation Can Improve the Functional Capacity and Quality of Life for Pneumoconiosis Patients: A Systematic Review and Meta-Analysis. (29th July 2020) - Zhao, Hulei; Xie, Yang; Wang, Jiajia; Li, Xuanlin; Li, Jiansheng
Abstract : This study evaluated the efficacy and safety of pulmonary rehabilitation (PR) for pneumoconiosis. We systematically searched PubMed, Embase, The Cochrane Library, Web of Science, SinoMed, CNKI, VIP databases and Wanfang Data from their inception to June 1, 2019. A systematic review and meta-analysis of randomized controlled trials (RCTs) of PR for pneumoconiosis was conducted and reported in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Two reviewers independently screened literature, extracted data, and assessed bias risk. All statistical analyses were performed using the RevMan software. Sixteen RCTs with 1307 subjects were ultimately included for analysis. Compared with routine treatment, PR was able to improve the 6-minute walking distance (mean difference (MD) 69.10, 95% confidence interval (CI) 61.95–76.25); the 36-Item Short Form Health Survey total score (MD 17.60, 95% CI 13.59–21.61); physical function score (MD 15.45, 95% CI 3.20–27.69); role physical score (MD 17.87, 95% CI 12.06–23.69); body pain score (MD 14.34, 95% CI 10.33–18.36); general health score (MD 20.86, 95% CI 16.87–24.84); vitality score (MD 11.66, 95% CI 0.18–23.13); social function score (MD 9.67, 95% CI 1.27–18.08); mental health score (MD 20.60, 95% CI 13.61–27.59); forced vital capacity (FVC) (MD 0.20, 95% CI 0.12–0.29); forced expiratory volume in 1 s (FEV1) (MD 0.23, 95% CI 0.09–0.38); FEV1% (MD 5.19, 95% CI 1.48–8.90); maximal voluntary ventilation (MD 4.47, 95% CI 1.14–7.81); reduction in the St. George's Respiratory Questionnaire score (MD -9.60, 95% CI -16.40 to -2.80); and the modified Medical Research Council Scale score. Furthermore, PR did not increase the FEV1/FVC (MD 3.61, 95% CI -3.43 to 10.65), nor the emotional score (MD 6.18, 95% CI -23.01 to 35.38) compared with the control. We found no reports of adverse events associated with PR. Thus, to some extent, PR can improve functional capacity and quality of life in patients with pneumoconiosis. However, these results should be interpreted with caution because of high heterogeneity. This trial is registered with registration number CRD42018095266 .